2017
DOI: 10.1038/ncomms15867
|View full text |Cite
|
Sign up to set email alerts
|

Sea level fall during glaciation stabilized atmospheric CO2 by enhanced volcanic degassing

Abstract: Paleo-climate records and geodynamic modelling indicate the existence of complex interactions between glacial sea level changes, volcanic degassing and atmospheric CO2, which may have modulated the climate system’s descent into the last ice age. Between ∼85 and 70 kyr ago, during an interval of decreasing axial tilt, the orbital component in global temperature records gradually declined, while atmospheric CO2, instead of continuing its long-term correlation with Antarctic temperature, remained relatively stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 73 publications
2
49
1
Order By: Relevance
“…It has recently been deduced, from ice core data covering the last 800 kyr, that the multimillennial trend of atmospheric CO 2 concentration and Antarctic temperature diverge when obliquity decreases (Hasenclever et al, 2017). It has recently been deduced, from ice core data covering the last 800 kyr, that the multimillennial trend of atmospheric CO 2 concentration and Antarctic temperature diverge when obliquity decreases (Hasenclever et al, 2017).…”
Section: Obliquity-driven Changes and The T G -Co 2 Relationshipmentioning
confidence: 99%
See 3 more Smart Citations
“…It has recently been deduced, from ice core data covering the last 800 kyr, that the multimillennial trend of atmospheric CO 2 concentration and Antarctic temperature diverge when obliquity decreases (Hasenclever et al, 2017). It has recently been deduced, from ice core data covering the last 800 kyr, that the multimillennial trend of atmospheric CO 2 concentration and Antarctic temperature diverge when obliquity decreases (Hasenclever et al, 2017).…”
Section: Obliquity-driven Changes and The T G -Co 2 Relationshipmentioning
confidence: 99%
“…It has recently been deduced, from ice core data covering the last 800 kyr, that the multimillennial trend of atmospheric CO 2 concentration and Antarctic temperature diverge when obliquity decreases (Hasenclever et al, 2017). Hasenclever et al (2017) suggested that the combination of marine volcanism at mid-ocean ridges and at hot spot island volcanoes might react to decreasing sea level and be a potential cause for this ΔT g -CO 2 divergence. Solid Earth modeling experiments have indicated that falling sea level might lead to enhanced magma and CO 2 production at mid-ocean ridges (e.g., Lund & Asimow, 2011).…”
Section: Obliquity-driven Changes and The T G -Co 2 Relationshipmentioning
confidence: 99%
See 2 more Smart Citations
“…EAGE SUN et al to shallower levels within basins and may even be expelled into the ocean or atmosphere (e.g., Hasenclever et al, 2017;Lee et al, 2016;Moussallam et al, 2017). For example, the synchronous and widespread extrusion of substantial volumes of methane-rich hydrothermal fluids, emanating from the tips of intruding igneous sills, may have triggered or contributed to ancient climate change events (e.g., Iyer, Schmid, Planke, & Millett, 2017;Jamtveit, Svensen, Podladchikov, & Planke, 2004;Reynolds et al, 2017;Svensen, Corfu, Polteau, Hammer, & Planke, 2012;Svensen et al, 2004).…”
mentioning
confidence: 99%